Advanced composite sandwich structure design for energy absorption applications: blast protection and crashworthiness - Tarlochan, F.; Ramesh, S.; Harpreet, S. (2012)
This paper describes an experimental investigation on the response of composite sandwich structures with tubular inserts to quasi-static compression. The performance parameters, namely the peak load, absorbed crash energy, specific energy absorption; average crushing load and crush force efficiency were evaluated. The composite sandwich specimens were fabricated from glass fiber, polystyrene foam and epoxy resin. The primary mode of failure observed was progressive crushing with the composites exhibiting high energy absorption capabilities and high crushes force efficiency. The mechanism of progressive crushing of the sandwich structures and its relation to the energy absorption capabilities was deliberated. Furthermore, a statistical analysis was performed to investigate the effects of the design variables and also to determine if there were interactions between these variables. Such information is vital in the design of polymer composite sandwich structures as energy absorbers. (C) 2012 Elsevier Ltd. All rights reserved